SAT0444 Cyclophosphamide Versus Mycophenolate for Systemic Sclerosis-Related Interstitial Lung Disease. (9th June 2015) - Volkmann, E.; Tashkin, D.; Clements, P.; Roth, M.; Furst, D.; Khanna, D.; Tseng, C.-H.; Arriola, E.; Elashoff, R.
Abstract : Background: While interstitial lung disease (ILD) is the leading cause of death in patients with systemic sclerosis (SSc), therapeutic options are limited. Although cyclophosphamide (CYC) demonstrated beneficial treatment effects at one year on forced vital capacity (FVC) and self-reported dyspnea (1), these improvements were not sustained at 2 years (2). Uncontrolled studies have demonstrated that mycophenolate (MMF) may improve SSc-ILD; however, no studies have directly compared safety and efficacy outcomes of CYC and MMF in SSc-ILD. Objectives: To conduct a double-blind, randomized, placebo-controlled trial (RCT) to compare the effects of CYC versus MMF on SSc-ILD outcomes Methods: Between September 2009 and January 2013, 142 SSc-ILD patients from 14 US centers were randomized to receive MMF (titrated as tolerated to 3.0 g/day in divided doses) for 2 years or oral CYC (titrated as tolerated to 2 mg/kg daily) for 1 year followed by an additional year on placebo (See Figure 1 ). Inclusion criteria were age ≥18 years, duration of disease ≤7 years from onset of the first non-Raynaud's SSc symptom, forced vital capacity (FVC) 40-80% predicted, hemoglobin-adjusted diffusing capacity for carbon monoxide (DLCO) ≥40% predicted (or 30-39% predicted if no evidence of pulmonary hypertension on echocardiogram and/or right heart catheterization), and evidence of any ground glass opacity on HRCT. The primary endpoint for the study was the FVC% predicted at 2 years, adjusted for baseline FVC. Key secondary endpoints included the transitional dyspnea index (TDI) and quantitative extent of lung fibrosis (QLF) and quantitative extent of ILD (QILD) on HRCT in both the whole lung (WL) and the zone of maximal involvement (ZM). Results: Among 142 participants (Mean [SD] age 52.3 [9.7] years), 74% were female and 59% had diffuse cutaneous involvement. The mean disease duration was 2.6 [1.8] years. Baseline pulmonary function was as follows (All Mean [SD]% predicted): FVC 66.5 [9.1]; Total lung capacity (TLC) 65.9 [10.9]; DLCO 54.0 [12.7]. The baseline mean health assessment assessment questionnaire disability index (HAQ-DI) score was 0.72 [0.7]. Baseline QLF scores were 32.5 [23.8] and 8.6 [6.8], for the ZM and WL, respectively. Baseline QILD scores were 63.4 [20.6] and 29.6 [13.7], for the ZM and WL, respectively. Among all participants, 86 (61%) completed the 24-month drug phase, while 20 (14%) withdrew drug prior to 24 months, but completed the 24-month visit. Adverse events were the primary reason for discontinuing treatment prematurely (40%). Twenty participants (14%) failed to complete the 24-month visit. There were 16 deaths during the study period. The majority of deaths (75%) occurred after stopping the study drug (4-17 months afterwards), and the predominant cause of mortality was respiratory failure related to SSc-ILD (56%). Conclusions: We herein describe the initial results of the first RCT to compare CYC versus MMF for SSc-ILD. Analyses of the primary and secondary endpoints are underway, the results of which will be available at the time of the EULAR presentation. References: Tashkin DP, et al. NEJM 2006;354:2655-2666. Tashkin DP, et al. Am J Respir Crit Care Med 2007;176:1026-34. Disclosure of Interest: None declared